Analysis of the influence of maintruss inclination angle on the aerodynamic characteristics of inverted trapezoidal steel joists - Peisong TENG; Cong WU; Min XIANG; Xiaobing LIU (Journal of Hebei University of Science and Technology, 2024)
Aiming at the problem that the change of the inclination angle of the main truss has a great influence on the aerodynamic characteristics of inverted trapezoidal steel trusses，taking a public-rail continuous steel truss as an example, the effect of main truss inclination on the aerodynamic characteristics of inverted trapezoidal steel truss was investigated. A simplified three-dimensional analysis model was established by using computational fluid dynamics (CFD) method for different main truss inclination angles to simulate the wind field of main turss sections with different main truss inclination angles. The differences of static wind aerodynamic coefficient, vortex vibration performance and flow field characteristics of main truss sections with different main truss inclination angles were analyzed. The results show that the lift and moment coefficients are significantly influenced by the change of main truss inclination, the lift coefficient of the steel truss is better when the inclination angle of the main truss is 10°, at this time the steel truss is subjected to smaller vertical wind load, and the moment coefficient of the steel joist is better when the inclination angle of the main truss is 0°, at this time the steel truss is subjected to smaller torsional wind load; the main truss inclination angle has a significant effect on its vortex excitation performance under 0° and 6° wind angle of attack conditions, and the vortex vibration performance is better at the main truss inclination angles of 2.5° and 5°;the deceleration phenomenon of wind velocity inside the steel truss decreases with the increase of main truss inclination, it contributes to internal traffic stabilization; the change of main truss inclination has obvious effect on the distribution of turbulent kinetic energy, the effect of increase of turbulent kinetic energy inside the steel truss decreases with the increase of main truss inclination and the effect of increase of turbulent kinetic energy on the leeward side of the steel truss strengthens. By comprehensively comparing multiple types of aerodynamic properties, the aerodynamic characteristics of steel trusses with main truss inclination angles of 5° are better. The influence of the change of main truss inclination angle on the aerodynamic characteristics and spatial flow field characteristics of inverted trapezoidal steel truss can provide a reference for the subsequent wind-resistant design of steel truss.